2017
DOI: 10.1007/s11882-017-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Diagnosis of Allergy to Anisakis spp.

Abstract: Isolated allergens help in the diagnosis of truly sensitized patients avoiding false positives due to cross-reactions. Their use is therefore highly recommended, especially when used as a combination of several relevant allergens. The use of purified allergens allows an accurate diagnosis and this has led to three important findings: (1) in addition to the digestive route of sensitization, occupational and non-digestive exposure seems to be clinically relevant. (2) The parasite appears as an important agent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 69 publications
3
34
0
Order By: Relevance
“…[50] to which all the Anisakis allergic patients previously showed sensitization [51]. This is not surprising as both Ani s 1 and 7 are encompassed within major allergens group, being products of the nematode excretory and secretory activity [5]. DQB1 � 05:02 that we identified as a strong protective factor against Anisakis sensitization is also a protective factor against house dust mite-sensitive allergic rhinitis [52].…”
Section: Hla and Anisakis Sensitizationsupporting
confidence: 60%
See 1 more Smart Citation
“…[50] to which all the Anisakis allergic patients previously showed sensitization [51]. This is not surprising as both Ani s 1 and 7 are encompassed within major allergens group, being products of the nematode excretory and secretory activity [5]. DQB1 � 05:02 that we identified as a strong protective factor against Anisakis sensitization is also a protective factor against house dust mite-sensitive allergic rhinitis [52].…”
Section: Hla and Anisakis Sensitizationsupporting
confidence: 60%
“…Likewise, one of the latest sources estimated 20 cases per year at European level [3], while a recently developed quantitative risk model suggested only in Spain between 7700 and 8320 of cases annually [4]. In light of these findings, Moneo et al [5] suggested a fifth anisakiasis form important from public health prospective that encompasses sensitized asymptomatic patients, otherwise healthy individuals with a high anti-Anisakis IgE titer that potentially underwent a subclinical or undiagnosed gastric anisakiasis without allergic symptoms. Due to the lack of clinical symptoms, this form of anisakiasis, which may account for more than 12% prevalence in some populations even using component-resolved diagnosis [6,7], is mainly detected in the course of epidemiological studies [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Fish are an intermediate host of the L3 infective larvae, which migrate through the digestive wall reaching abdominal organs such as liver, ventral or dorsal muscles, and surrounding connective tissue. Humans are an accidental host of larval stage L3, which in many cases causes gastrointestinal or allergic manifestations (Baird et al, 2014;Nieuwenhuizen & Lopata, 2014;Moneo et al, 2017). These parasites have been found in several fish species, including the Chilean hake (Merluccius gayi gayi) (Jofré et al, __________________ Corresponding editor: Leonardo Abitia 2008).…”
mentioning
confidence: 99%
“…Recently-developed molecular testing methods may be used to identify cross-reactivity between the protein from Anisakis and other allergenic sources such as crustaceans. When a patient is diagnosed with hypersensitivity to Anisakis, a molecular test determines the exact protein to which they are sensitised and may therefore be useful for predicting the potential development of reactions to allergens that show cross-reactivity [21,22].…”
Section: Discussionmentioning
confidence: 99%